SYNTHESIS OF B VITAMINS BY MICROORGANISMS IN SOIL (Scientific journal of the Fergana State University, 2024)
This article is devoted to the synthesis of vitamins in the soil. The article discusses the features of the synthesis of B vitamins in the soil by cellulose-destroying microorganisms - bacteria, fungi and actinomycetes in the environment of various carbon sources. At the same time, the results obtained on the basis of the experiments of various scientists who conducted research on this topic were analyzed, compared and summarized. As a result of the study and generalization of the conducted scientific research, conclusions were drawn about the productivity and other features of the synthesis of B vitamins in the soil by various microorganisms.